Physicians’ perceptions and awareness of adverse effects of proton pump inhibitors and impact on prescribing patterns - Awad, Abdelmoneim; Al-Tunaib, Abdulaziz; Al-Saraf, Sarah (Frontiers in Pharmacology, 2024)
Background: Heightened scrutiny surrounds the inappropriate use of proton pump inhibitors (PPIs) due to concerns regarding potential serious adverse effects (AEs). Understanding the impact of these AEs on real-world practice is crucial. This study aimed to assess physicians' perceptions, experiences, awareness, and beliefs regarding published data on potential AEs associated with PPIs. Additionally, it sought to determine alterations in PPI prescribing patterns resulting from these AEs, explore attitudes towards PPI use, and ascertain recommendations for PPI use in clinical scenarios with varying levels of risk for upper gastrointestinal bleeding (UGIB).Method: A quantitative, cross-sectional study utilized a self-administered questionnaire, inviting 282 physicians from 55 primary healthcare centers and 334 internal medicine physicians from 7 governmental hospitals to participate.Results: With a response rate of 87.8% (541/616), 74% (95% CI: 70.2-77.7) of respondents were somewhat or very familiar with published data on PPI AEs. Among the familiar, 69.5% (CI: 65.2-73.5) had somewhat or very much changed their PPI prescribing patterns. General concerns about AEs when prescribing PPIs were reported by 62% (CI: 56.7-65.1). Respondents displayed awareness of a median (IQR) of 15 (9) different AEs associated with long-term PPI use, including osteoporosis or osteopenia (90.2%), hypomagnesemia (81.5%), vitamin B12 deficiency (80.6%), and bone fracture (80.0%). Respondents believed that PPIs elevate the risk for a median (IQR) of 7 ( 6) different AEs, with osteoporosis or osteopenia (81.8%) being the most common, followed by hypomagnesemia (67.1%), and vitamin B12 deficiency (62.3%). The most common strategies for PPI de-escalation were PPI discontinuation (61%) and using PPI on-demand/as-needed (57.9%).The majority (87.4%) agreed or strongly agreed that PPI overuse is prevalent in Kuwait and 78.2% emphasized the necessity for large-scale education on rational PPI use for medical staff and the public. In the UGIB prevention scenarios, 43.6% recommended appropriately the PPI discontinuation in the minimal-risk scenario, while 56% recommended appropriately the PPI continuation in the high-risk scenario. Associations and comparative analyses revealed predictors influencing physicians' practices and attitudes toward PPI usage.These findings lay the foundation for future research and targeted interventions aimed at optimizing PPI prescribing practices and ensuring patient safety.